Enhancing the energy efficiency of vapour compression refrigerator system using R600a with graphene nanolubricant - T. O. Babarinde; S. A. Akinlabi; D. M. Madyira; F. M. Ekundayo (Energy Reports, 2020)
The use of graphene nanolubricant to enhance the performance of eco-friendly refrigerant (R600a) in a vapour compression system was investigated. The graphene nanoparticles were dispersed in the base lubricant and prepared for three different samples of graphene nanolubricant concentration of 0.2, 0.4 and 0.6 g/L, the nanolubricant concentrations were investigated in 50, 60 and 70g of R600a refrigerant each. The performances were compared with the base lubricant (mineral oil). The result showed that R600a performed better in graphene nanolubricant compared to the base lubricant in terms of pull-down time, COP, power consumption, cooling capacity. Therefore, graphene nanolubricant can be used as a drop-in replacement for pure mineral oil in the vapour compression system.
Keywords: 330; COP; Graphene nanolubricant; GWP; ODP; Power consumption